Anxious Uncertainty and Reactive Approach Motivation (RAM) for Religious, Idealistic, and Lifestyle Extremes. (9th September 2013) - McGregor, Ian; Prentice, Mike; Nash, Kyle
Abstract : Reactive Approach Motivation (RAM) theory proposes that the personal uncertainty arising from motivational conflict causes anxiety, and that anxiety draws people to extremes because extremes activate approach‐motivated states that automatically downregulate anxiety. Five new studies consolidate existing evidence for the RAM view of uncertainty‐related threats and reactive extremism. In Studies 1–3, religious, idealistic, and RAM reactions after agentic, communal, and mortality threats were most extreme when threat‐relevant goals had been implicitly primed to create motivational conflict. In Study 4 uncertainty predicted extreme reactions only if goal conflict had been experimentally manipulated. In Study 5 personal uncertainty uniquely predicted lifestyle extremes among undergraduates whose educational goals were conflicted by a labor disruption at their university. Results converge on the conclusion that uncertainty‐related threats cause defensively extreme RAM reactions only if they arouse personal uncertainty about active goals. Results suggest that policies and programs to support the prosocial and/or nonextreme goals, ideals, and identifications of at‐risk people would reduce their motivation for antisocial extremism.